Pohybové chvilky a kinetické vyučování ve školním režimu žáků mladšího školního věku - Feltlová, Dana; Němcová, Petra; Vodehnalová, Dagmar (Optimální působení tělesné zátěže a výživy, 2006)
All information was obtained as based on a method inquiry. From the total of a 70- asked, filled in 50 respondents their forms. 48 respondents clearly specified the active's broken and can correctly classify. We could say, that active's breaks are very often realized in practice. On the other hand the kinetic classes were not able to clearly define about 50 % respondents. In spite of the number, We think, that majority of teachers place this activity in their lessons. We suppose nowadays, when sedentary lifestyle with little moving is common, it is very necessary to add some activity into system of education of younger aged pupils. Active's breaks and mostly classes with moving may be a good occasion for making a contact between a teacher and a pupil. The teacher sees the child working in different position, not only as one sitting at a desk. The teacher can find out a position of the pupil in the class – group, leading and authoritative ability or his participation in schoolwork. A kinetic class is certainly a good sign, which could uncover the circumstances leading into chicane. Lessons with activity help to bring out or explain new problems and it is excellent way for repeating these tasks. It becomes a good way how to reduce inattention and fatigue. This break helps pupils to meet their basic needs as moving without any discussion.
Keywords: Exercise Movement Techniques; Schools; Physical Education and Training; Humans; Child; průzkumy a dotazníky; lidé; studenti; dítě; techniky cvičení a pohybu; Surveys and Questionnaires; Teaching; školy; vyučování; tělesná výchova; Students